Mixotrophic growth of microalgae on crude glycerol - Effects on productivity and biochemical composition - Svensson, Oscar (My University, 2016)
The potential of microalgae to be grown for fuel purposes have long been known and have gained a lot of interest from the biofuel industry in recent years. This potential comes from being an environmentally friendly fuel alternative, utilizing the fast growing photosynthesizing algae as production organisms in a world where demand is constantly rising. However, fuels are not the only use for these organisms and other products of higher value could also be obtained. By looking wider and also investigating modes of growth not solely dependent on photosynthesis the useful applications and growth areas can be increased for example in regions with less sunshine. The aim of this study was to identify species of microalgae capable of utilizing glycerol as an added source of energy and carbon to increase productivity. Glycerol was chosen because it is a readily available byproduct from an increasing global biodiesel production. In this study we screened a small number of species connected to the genus Scenedesmus among green algae with regards to their growth rates, ability to utilize glycerol as a source of carbon and energy and their production of carotenoids. The species Ankistrodesmus falcatus was identified as having a fast exponential production (153.9 ± 48.6 mgL-1d-1) and it was further increased by addition of glycerol to the media (280.5 ± 10.8 mgL-1d-1). By further optimizing the growth conditions and increasing glycerol addition to this species an exponential production of 458.7 ± 14.4 mgL-1d-1 was measured. Productivity of both fatty acids and carotenoids was increased significantly verifying the potential of using glycerol addition to increase production, possibly in combination with lower light conditions.
Keywords: Energi; Livsvetenskaper; Industriell bioteknik; Bioprocessteknik; Biomaterial; Energy; Life Science; Industrial Biotechnology; Bioprocess Technology; Bio Materials